On the brink of power: An inquiry into emerging power through international political economy - Jack Houghton (Journal of Global Faultlines)
This article examines the rise of emerging powers through the lens of international political economy (IPE). While scholarship focuses on established emerging powers such as China and India, a subset of underrepresented countries including Indonesia, Turkey, and South Africa warrant deeper analysis. Contextualizing their ascent through IPE processes highlights how these regional leaders-in-the-making transformed from developing to emergent status amid evolving global power dynamics. The research explores their roles within a Western-dominated order facing challenges to its liberal democratic foundations. By unpacking the implications of their non-liberal capitalist development paths, it provides a refreshed perspective on whether these newly influential states pose a threat to US hegemony or are simply manifestations of an increasingly multipolar world order.